Harmonization of Water Management Regulations Post Constitutional Court Decision Number 85/PUU-XI/2013 in the Perspective of al-Maslahah al-Mursalah - Pambudi, Roikhan Arif (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2025)
Background. The Constitutional Court has annulled Law Number 7 of 2004 concerning Water Resources because it is contrary to the 1945 Constitution of the Republic of Indonesia. The Court returned all forms of water resource regulation to Law Number 11 of 1974 concerning Irrigation. The legal changes have an impact on water management companies in Indonesia. Aim. This article examines the legal consequences of Constitutional Court Decision Number 85/PUU-XI/2013 on corporate water governance from the perspective of al-Maslahah al-Mursalah. Methods. Normative legal studies, using the legislative, case, and conceptual approaches. Data were obtained through literature studies, and analyzed using qualitative descriptive analysis. Results. Companies that continue to utilize water resources without clear authority can be categorized as a form of theft or seizure of water resources. According to Article 15 Paragraph (2) of the Water Law, this is detrimental to the state. The Water Law does not fully emphasize that only the state has the right to manage water resources. Based on al-maslahah al-mursalah with the right to exploit water resources, water is a source of livelihood and hifdz a-maal. The government should make strict regulations in accordance with al-maslahah al-mursalah to create benefits and avoid damage (jalb al-mashalih dar'u wa al-mafasid).